On the Characteristics of Adjective Reduplication in Indonesian and Chinese and its Implications for Chinese Language Teaching - Surinah (Mandarinable: Journal of Chinese Studies, 2026)
This article presents a contrastive analysis of adjective reduplication in Indonesian and Chinese, two typologically distinct languages. Although reduplication is a common linguistic device across languages, its forms and functions vary considerably, posing particular challenges for Indonesian learners of Chinese. Drawing on dictionary, corpus, and literary data from both languages, the study compares adjective reduplication in terms of structural forms, syntactic functions, and grammatical marking mechanisms. Five similarities are identified: both allow word-class change; function as attributives, adverbials, predicates, and objects; enhance descriptiveness and coloristic meaning; exhibit increased intensity (quantity iconicity); and resist degree adverbs. Four differences are found: Chinese has five reduplication patterns (vs. eleven in Indonesian); Chinese uses syllable-based segmentation (vs. word-based); Chinese employs the particle de (vs. affixes and prepositions); and Chinese encodes degree only (vs. degree + plural quantity). Pedagogical implications for Indonesian learners include contrastive restructuring for structural differences, function-first sequencing for grammatical marking, and semantic constraint awareness for focus differences, complemented by the strategic use of cross-linguistic commonalities as positive transfer anchors. The study extends quantity iconicity to cross-typological comparison and offers a systematic contrast of grammatical marker systems (particles vs. affixes/prepositions) within a corpus-based, multi-dimensional framework.